The Impact of Discipline and Work Environment of ASN Employees on the Secretariat of DPRD Banggai Regency - Adrian Polim; Sri Mulyaningsih Kamaru; Suharman Suharman (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the influence of discipline and work environment on the performance of ASN in the Secretariat of the Banggai Regency DPRD. The data used was quantitative by involving 45 State Civil Apparatus employees as samples. Data was collected through questionnaires and analysis with the help of SPSS. The results of the regression analysis show similarities Y = 7,155 + 0,250X1 + 0,354X2. The value of the correlation coefficient is 0.438 which has a fairly strong relationship between variables. The value of the Determination coefficient means that the contribution of the influence of independent variables on the bound variable is 19.2% and the rest is influenced by other factors outside of this study. The t-test showed that the work discipline variable had an effect but was not significant on employee performance with thitung1,941 < ttabel 2,018 sedangkan variabel lingkungan kerja berpengaruh signifikan terhadap kinerja karyawan dengan nilai thitung 2,605 > ttabel 2,018. The f test shows that the variables of work discipline and work environment simultaneously have a significant influence on the employee performance variables with significance values 4,975 > ttabel 3,22.